Activity of forest specialist bats decreases towards wind turbines at forest sites. Issue 10 (18th July 2022) - Ellerbrok, Julia S.; Delius, Anna; Peter, Franziska; Farwig, Nina; Voigt, Christian C.
Abstract: Worldwide, wind turbines are increasingly being built at forest sites to meet the goals of national climate strategies. Yet, the impact on biodiversity is barely understood. Bats may be heavily affected by wind turbines in forests, because many species depend on forest ecosystems for roosting and hunting and can experience high fatality rates at wind turbines. We performed acoustic surveys in 24 temperate forests in the low mountain ranges of Central Germany to monitor changes in the acoustic activity of bats in relation to wind turbine proximity, rotor size, vegetation structure and season. Call sequences were identified and assigned to one of three functional guilds: open‐space, edge‐space and narrow‐space foragers, the latter being mainly forest specialists. Based on the response behaviour of bats towards wind turbines in open landscapes, we predicted decreasing bat activity towards wind turbines at forest sites, especially for narrow‐space foragers. Vertical vegetation heterogeneity had a strong positive effect on all bats, yet responses to wind turbines in forests varied across foraging guilds. Activity of narrow‐space foragers decreased towards turbines over distances of several hundred metres, especially towards turbines with large rotors and during mid‐summer months. The activity of edge‐space foragers did not change with distance to turbines or season, whereas the activity of open‐space foragers increased close to turbines in late summer. Synthesis and applications . Forest specialist bats avoid wind turbines in forests over distances of several hundred metres. This avoidance was most apparent towards turbines with large rotors. Since forests are an important habitat for these bats, we advise to exclude forests with diverse vegetation structure as potential wind turbine sites and to consider compensation measures to account for habitat degradation associated with the operation of wind turbines in forests. Abstract : Forest specialist bats avoid wind turbines in forests over distances of several hundred metres. This avoidance was most apparent towards turbines with large rotors. Since forests are an important habitat for these bats, we advise to exclude forests with diverse vegetation structure as potential wind turbine sites and to consider compensation measures to account for habitat degradation associated with the operation of wind turbines in forests. Zusammenfassung: Weltweit werden Windenergieanlagen zunehmend an Waldstandorten errichtet, um die Ziele der nationalen Klimastrategien erreichen zu können. Die Auswirkungen auf die biologische Vielfalt sind jedoch kaum bekannt. Fledermäuse könnten durch Windenergieanlagen in Wäldern stark beeinträchtigt werden, da viele Arten auf Waldökosysteme als Rückzugs‐ und Jagdgebiete angewiesen sind und gleichzeitig eine hohe Sterblichkeitsrate an Windenergieanlagen aufweisen können. Wir führten akustische Untersuchungen in 24 gemäßigten Wäldern im deutschen Mittelgebirge durch, um Veränderungen in der akustischen Aktivität von Fledermäusen in Abhängigkeit von der Nähe zu Windenergieanlagen, der Rotorgröße, der Vegetationsstruktur im Wald und der Jahreszeit zu beobachten. Die Rufsequenzen wurden identifiziert und einer von drei funktionalen Gilden zugeordnet: Offenraumjäger, Jäger an Strukturen und Waldspezialisten. Auf der Grundlage der Reaktion von Fledermäusen auf Windenergieanlagen in offenen Landschaften sagten wir eine abnehmende Fledermausaktivität in Richtung von Anlagen an Waldstandorten voraus, insbesondere für Waldspezialisten. Die vertikale Vegetationsheterogenität hatte einen starken positiven Effekt auf alle Fledermausgilden, während die Reaktionen auf Windenergieanlagen in Wäldern je nach funktionaler Gilde variierten. Die Aktivität von Waldspezialisten nahm in Richtung der Anlagen über Entfernungen von mehreren hundert Metern ab, insbesondere bei Anlagen mit großen Rotoren und während der Hochsommermonate. Die Aktivität der Jäger an Strukturen änderte sich weder mit der Entfernung zu den Anlagen noch der Jahreszeit, während die Aktivität der Offenraumjäger im Spätsommer in der Nähe der Windenergieanlagen zunahm. Synthese und Anwendungen . Auf Wälder spezialisierte Fledermäuse meiden Windenergieanlagen in Wäldern über Entfernungen von mehreren hundert Metern. Dieses Meidungsverhalten war in der Nähe von Anlagen mit großen Rotoren am deutlichsten. Da Wälder ein wichtiger Lebensraum für diese Fledermäuse sind, raten wir dazu, Wälder mit diverser Vegetationsstruktur als potenzielle Standorte für Windenergieanlagen auszuschließen und Ausgleichsmaßnahmen in Betracht zu ziehen, um die mit dem Betrieb von Windenergieanlagen in Wäldern verbundene Habitatdegradierung zu kompensieren.